Adaptation to coastal environmental change in Louisiana: an analysis of local and state environmental governance relationships - Molloy, Michael Shannon (Kansas State University, 2020)
Coastal Louisiana has lost over 1900 square miles of land since 1932, causing the collapse of ecosystems and threatening the well-being of human populations. However, Coastal Louisiana is not impacted solely by land loss, but rather multiple anthropogenic and non-anthropogenic mechanisms that are causing rapid environmental change to occur across the region. Recent estimates place the economic costs of environmental change in Louisiana’s coastal areas at $37 billion by 2050. This study examines the alignment of adaptation strategies employed by the State of Louisiana, and Lafourche, Terrebonne, and Plaquemines Parishes. In a case study analysis, I utilize key actor interviews, document analyses, and participant observation. Expanding upon a categorical framework of community responses to environmental hazards, I developed six categories of possible community responses to environmental change. Using this framework, I analyzed the alignment of environmental policies employed by the state and local governments in Coastal Louisiana. When analyzing documents alone, results indicate that parishes and the State of Louisiana are aligned when choosing and implementing environmental change adaptation strategies However, an analysis of key actor interviews within the parishes reveal greater variation in adaptation strategies pursued at a local scale. My findings indicate that this variation of adaptation strategies at the local scale can be explained, in part, by local political and industrial influences Additionally, I found that the Coastal Protection and Restoration Authorities emphasis on using technical solutions as the preferred adaptation strategy, fails to account for the agencies goal of protecting unique cultures. This work advances scholarship in political ecology, and climate change adaptation literature, by expanding the possible community adaptation responses, answering the complex questions in climate change literature, and examining the impacts of politics on responses to environmental degradation.
Keywords: Coastal Louisiana; Land loss; Enivronmental Change; Adaptation; Governance; CPRA